Early-life exposure to the Chinese famine of 1959-61 and risk of Hyperuricemia: results from the China health and retirement longitudinal study - Wenqiang Zhang; Rongsheng Luan (BMC, 2020)
Abstract Background Short-term starvation has been related to hyperuricemia. However, little is known about the long-term effect of early-life exposure to famine on hyperuricemia risk in adulthood. Methods The analysis included 2383 participants from the China Health and Retirement Longitudinal Study in 2015. Hyperuricemia was diagnosed as serum uric acid ≥7 mg/dL in men and serum uric acid ≥6 mg/dL in women. Famine exposure subgroups were defined as unexposed (born between October 1, 1962, and September 30, 1964), fetal-exposed (born between October 1, 1959, and September 30, 1961), and early-childhood exposed (born between October 1, 1956, and September 1, 1958). The association between early-life famine exposure and hyperuricemia risk was assessed using multivariate logistic regression. Results The prevalence of hyperuricemia in the unexposed, fetal-exposed, and early-childhood exposed participants was 10.7, 14.1, 11.1%, respectively. Compared with unexposed and early-childhood exposed participants combined as an age-balanced control, fetal-exposed participants showed an increased risk of hyperuricemia in adulthood (OR = 1.41; 95% CI: 1.06-1.88), after adjusting for gender, marital status, famine severity, residence, smoking, drinking, BMI, hypertension, and diabetes. The famine effect on hyperuricemia was accentuated by overweight or obesity (P for interaction = 0.042). Compared with unexposed and BMI < 24 kg/m2 participants, the OR (95%CI) of hyperuricemia was 3.66 (2.13-6.30) for fetal-exposed and overweight/obesity participants. However, combined unexposed and early-childhood exposed participants as an age-balanced control, the interaction of famine exposure and BMI was not statistically significant (P for interaction = 0.054). Conclusion Famine exposure in the fetal stage was associated with an increased risk of hyperuricemia in adulthood.